A BIBLIOMETRIC ANALYSIS OF CUSTOMER-CONSUMER ENGAGEMENT BEHAVIOR IN SOCIAL MEDIA - ATHAR RISWANDA, MUHAMMAD; Martini, Erni; Tantra, Tarandhika (Fakultas Ekonomi dan Bisnis, Telkom University., 2025)
Customer engagement behavior is an important outcome that serves as a primary objective of social media marketing. However, both practitioners and academics still face limitations in gaining comprehensive insights into this area. The limited number of studies that explain the development of research on customer engagement behavior remains an issue that needs to be addressed. This study aims to fill this gap by conducting a bibliometric analysis of the concept of customer engagement behavior on social media using the VOSviewer software. The data were collected based on keyword searches in the Scopus database. From the search results, 910 relevant articles published between 2009 and 2022 were identified. The findings indicate that Facebook is the most frequently occurring keyword in studies on customer engagement behavior in social media. The United States is the country with the highest number of articles in this field. Future research opportunities related to customer engagement behavior include studies on emotion, content creators, and automated content analysis. This research contributes by providing a comprehensive mapping of studies on customer engagement behavior over the past 12 years. It is expected to serve as a valuable reference and guide for other researchers in conducting and determining research themes in the future.